Pathotype characterization of Aphanomyces euteiches isolates collected from pea breeding nurseries - Moussart, Anne; Lavaud, Clément; Onfroy, Caroline; Leprévost, Théo; Pilet-Nayel, Marie-Laure; Le May, Christophe (Frontiers in Plant Science, 2024)
Aphanomyces euteiches Drechsler is an oomycete pathogen that affects legume crops, causing root rot, a severe disease of peas (Pisum sativum L.) worldwide. While significant research progress has been made in breeding pea-resistant varieties, there is still a need for a deeper understanding of the diversity of pathogen populations present in breeding nurseries located in various legume-growing regions around the world. We analysed the diversity of 51 pea-infecting isolates of A. euteiches, which were recovered from four American (Athena, ID; Le Sueur, MN; Mount Vernon, WA; Pullman, WA) and three French (Riec-sur-Belon, Templeux-le-Guérard, Dijon) resistance screening nurseries. Our study focused on evaluating their aggressiveness on two sets of differential hosts, comprising six pea lines and five Medicago truncatula accessions. The isolates clustered into three groups based on their aggressiveness on the whole pea set, confirming the presence of pathotypes I and III. Pathotype I was exclusive to French isolates and American isolates from Athena and Pullman, while all isolates from Le Sueur belonged to pathotype III. Isolates from both pathotypes were found in Mount Vernon. The M. truncatula set clustered the isolates into three groups based on their aggressiveness on different genotypes within the set, revealing the presence of five pathotypes. All the isolates from the French nurseries shared the same Fr pathotype, showing higher aggressiveness on one particular genotype. In contrast, nearly all-American isolates were assigned to four other pathotypes (Us1, Us2, Us3, Us4), differing in their higher aggressiveness on two to five genotypes. Most of American isolates showed higher aggressiveness than French isolates within the M. truncatula set. These results provide valuable insights into A. euteiches pathotypes, against which the QTL and sources of resistance identified in these nurseries displayed effectiveness. They also suggest a greater adaptation of American isolates to alfalfa, a more widely cultivated host in the United States.